2019
DOI: 10.1371/journal.pone.0222902
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of enclosed hydration effects in the binding free energy estimation of dopamine D3 receptor complexes

Abstract: Confined hydration and conformational flexibility are some of the challenges encountered for the rational design of selective antagonists of G-protein coupled receptors. We present a set of C3-substituted (-)-stepholidine derivatives as potent binders of the dopamine D3 receptor. The compounds are characterized biochemically, as well as by computer modeling using a novel molecular dynamics-based alchemical binding free energy approach which incorporates the effect of the displacement of enclosed water molecule… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Results from these functional assays demonstrated bromophenol 1 as a full D 3 R agonist and 3 as a full D 3 R/D 4 R agonist (order of agonist effect: D 4 R > D 3 R). From the docking study, bromophenols 1 – 3 were predicted to interact at OBS of D 3 R surrounded by the helices III, V, VI, and VII with Cys114, His345, Phe345, Phe346, Ser192, and Val189 . Likewise, for D 4 R binding, 1 – 3 were predicted to interact with Val193 and Ser197 in helix V and with Asp115 in helix III via H-bond interactions, which are crucial residues for drug binding to the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Results from these functional assays demonstrated bromophenol 1 as a full D 3 R agonist and 3 as a full D 3 R/D 4 R agonist (order of agonist effect: D 4 R > D 3 R). From the docking study, bromophenols 1 – 3 were predicted to interact at OBS of D 3 R surrounded by the helices III, V, VI, and VII with Cys114, His345, Phe345, Phe346, Ser192, and Val189 . Likewise, for D 4 R binding, 1 – 3 were predicted to interact with Val193 and Ser197 in helix V and with Asp115 in helix III via H-bond interactions, which are crucial residues for drug binding to the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Implicit solvent models have been proposed as one way to circumvent these latter problems, but implicit solvent models still suffer from the overlap issue and recent studies have shown that the neglect of explicit waters can lead to considerable artifacts. 89 At the time Zwanzig published his equation, there was no way to evaluate the ensemble average for a molecular system of interest. But by the mid-1980s, molecular dynamics and Monte Carlo methods and the evolution of computers made it possible to apply the equation to real systems, as first demonstrated in the laboratories of McCammon 90 and Jorgensen.…”
Section: ■ Rigorous Binding Free Energy Methodsmentioning
confidence: 99%
“…Explicit solvent also makes the sampling of protein domain motions difficult, due to water diffusion, which lengthens the time scale of such motions. Implicit solvent models have been proposed as one way to circumvent these latter problems, but implicit solvent models still suffer from the overlap issue and recent studies have shown that the neglect of explicit waters can lead to considerable artifacts …”
Section: Rigorous Binding Free Energy Methodsmentioning
confidence: 99%
“…Destabilization of D3 inactive state(s) and flexibility of the ligands are among the elements that the most recent model available is proposing ( Ferraro et al., 2020 ). Molecular recognition steps, changes in hydration of the ligand binding pocket and ligand dependent receptor configuration changes are also important considerations for D2 and D3 in particular when docking flexible ligands and establishing comparisons ( Pal et al., 2019 ). Native system pharmacology studies are due to confirm the relevance of the observed in vitro differences.…”
Section: Section 3 Dr Ligands and Scz Therapies The New Wave Of Ligmentioning
confidence: 99%